New forms of production organization: pearl companies - L. V. Kuropatkina (Russian Journal of Economics and Law)
Objective: to develop a management system for new types of companies (pearl organizations).Methods: abstract-logical, methods of analysis and synthesis of theories and patterns of development of managerial approaches in economics.Results: the study of the evolution of organizational structures in production management within the concept of spiral dynamics by K. Graves, K. Kovan, and D. Beck, combined with the analysis of current problems of domestic corporate management leads to the formulation of the problem of choosing the forms of company management that best correspond to the current state and prospects of the formation of a new intellectual economy. In this context, G. B. Kleiner proposed the concept of pearl enterprises as organizations that ensure the long-term effectiveness of the activities of each employee, a team of departments and the company as a whole by expanding the range and increasing the flexibility of formal and informal, hierarchical and non-hierarchical management models used in its various segments. Such companies may be built by transforming the socalled turquoise organizations, which represent the most advanced form of democratic system management to date. The article analyzes the key problems of creating pearl companies by transforming the existing classical hierarchies, including the transformation of turquoise organizations into pearl ones.Scientific novelty: the requirements for the work of HR management in pearl companies are formulated, taking into account the increasing importance of creative intellectual work. The expediency of expanding the corpus of pearl organizations in the Russian economy under digitalization is substantiated.Practical significance: the main provisions and conclusions of the article can be used in scientific and pedagogical activities when considering the concept of pearl companies and developing modern approaches to HR management in organizations.